Identification of DLEC1 D215N Somatic Mutation in Formalin Fixed Paraffin Embedded Melanoma and Melanocytic Nevi Specimens - Ricardo Vieira; Maria José Simões; Susana Carmona; Conceição Egas; Carlos Faro; Américo Figueiredo (Journal of Skin Cancer)
DLEC1 has been suggested as a tumor suppressor gene in several cancers. DLEC1 D215N somatic mutation (COSM36702) was identified in a melanoma cell line through whole genome sequencing. However, little is known about the implication and prevalence of this mutation in primary melanomas or in melanocytic nevi. The aim of this study was to genotype DLEC1 D215N mutation in melanoma tissue and melanocytic nevi samples to confirm its occurrence and to estimate its prevalence. Primary melanomas (n=81) paired with synchronous or asynchronous metastases (n=21) from 81 melanoma patients and melanocytic nevi (n=28) were screened for DLEC1 D215N mutation. We found the mutation in 3 primary melanomas and in 2 melanocytic nevi, corresponding to a relatively low prevalence (3.7% and 7.1%, resp.). The pathogenic role of DLEC1 215N mutation is unclear. However, since the mutation has not been previously described in general population, its involvement in nevogenesis and melanoma progression remains a possibility to be clarified in future studies.